1999
DOI: 10.1002/(sici)1099-1263(199911/12)19:6<431::aid-jat594>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of long-term administration of the antioxidant stobadine on exploratory behaviour in rats of both genders

Abstract: Stobadine (STO) is a prospective neuro‐ and cardioprotective drug with high antioxidative properties. The aim of this study was to ascertain the effect of long‐term administration of STO on exploratory behaviour and habituation processes in adult virgin female and male rats. Stobadine was administered by oral gavage in a single dose of 50 mg kg−1 day−1 for a total of 56 days. The animals were tested for exploratory behaviour—intensity of motor and vertical activity in an open field test in three blocks of meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…We used a non-invasive ethological approach of behavioral analysis. Both derivatives originate from stobadine (STO), whose molecule was studied in detail and no adverse effects were observed (Gajdošíková et al , 1995; Balonová et al , 1991; Dubovický et al , 1999). STO is an optic stereoisomer of the neuroleptic drug γ-carboline Carbidine ® (Barkov, 1973).…”
Section: Discussionmentioning
confidence: 99%
“…We used a non-invasive ethological approach of behavioral analysis. Both derivatives originate from stobadine (STO), whose molecule was studied in detail and no adverse effects were observed (Gajdošíková et al , 1995; Balonová et al , 1991; Dubovický et al , 1999). STO is an optic stereoisomer of the neuroleptic drug γ-carboline Carbidine ® (Barkov, 1973).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that coping behavior in novelty could be a sensitive indicator of behavioral toxicity, complex habituation analyses are omitted in most of the neurotoxicity studies. In our previous studies, we thoroughly investigated habituation of exploratory behavior in neurobehavioral toxicities, and the results obtained are of relevance for evaluating behavioral processes in the open field in a more complex way (Dubovický et al ., 1997a , b ; 1999a , b ; 2004 ).…”
Section: Basic Procedures Of Neurobehavioral Testingmentioning
confidence: 99%
“…In our current experimental practice we test animals repeatedly. Repeated testing in an open field test enables a more complex evaluation of the data obtained, such as habituation processes (Dubovický et al ., 1997a ; 1999a ). In a series of experiments in which we investigated the effect of neonatal anoxia on motor activity in the open field at the time around weaning (single anoxia induced on postnatal days 2, 3, 4 or 5 in duration of 10, 15, 20 or 25 min), we found a decrease in motor activity compared to controls in all time intervals.…”
Section: Most Important Issues To Be Taken Into Account In Neurobehavmentioning
confidence: 99%
“…(for review see Juranek et al , 2010). Series of toxicological studies including acute, subchronic and chronic toxicity tests with STB on various animals concluded that STB was safe and did not possess any severe adverse effects within the potential pharmacological range (Gajdošíková et al , 1995, Dubovický et al , 1999). However, a non-specific α-adrenolytic (Kvaltinova et al , 1986) and H 1 -antihistaminic side effects were reported (Lukovic & Machova, 1988).…”
Section: Introductionmentioning
confidence: 99%